Assessing Shallow Groundwater Quality Around the Sheba Leather Tannery Area, Wikro, North Ethiopia: A Geophysical and Hydrochemical Study - Kaleab Adhena Abera; Berhane Abrha Asfaw; Yonatan Garkebo Doyoro; Tesfamichael Gebreyohanes; Abdelwassie Hussien; Gebremedhin Berhane; Miruts Hagos; Abadi Romha; Kristine Walraevens (Geosciences, 2024)
This study aimed to investigate the shallow groundwater status around the Sheba Leather Tannery area, Wikro, North Ethiopia, through geophysical and hydrochemical methods. Seventeen Vertical Electrical Soundings (VESs) acquisitions, 4 upstream and 13 downstream, of the leather tannery area were conducted. Using the data, four geoelectric profiles were generated. The aquifers’ geoelectrical layers, depth, and lateral extent were delineated. The VES curves depicted three to four resistivity layers. These alternating layers of low, moderate, and high resistivity values, traced at different VES points, were attributed to the formations’ composition and the groundwater quality status. Besides the geophysical survey, 32 water samples were collected from the area. Parameters such as electrical conductivity (EC), total dissolved solids (TDSs), pH, major ions, and heavy metals were analyzed. Moreover, PHREEQC was used to determine the groundwater mineral saturation indices where most minerals, except halite, were found supersaturated. The quality status for drinking purposes was also evaluated using the water quality index (WQI), and the water was classified as good (56.3%), poor (37.5%), and very poor (6.2%). The sodium adsorption ratio (SAR) and the percentage of sodium (Na+%) were calculated, and the results indicated that the water is suitable for direct use in irrigation.